The HUBUNGAN PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA BALITA YANG MENGAKIBATKAN STUNTING DI WILAYAH UPT PUSKESMAS ULAWENG - Arfan Arfan Nur; Nurul Annisa`` (Jurnal Berita Kesehatan, 2022)
Stunting is one of the failures to achieve physical development as measured by height for age Objective: The purpose of this study was to determine the relationship between supplementary feeding (PMT) to toddlers that resulted in stunting at the UPT Puskesmas Ulaweng, Ulaweng District. Methods: This study uses a correlation analytic research method, which aims to analyze the relationship between parental knowledge and supplementary feeding (PMT) in stunting toddlers, by describing a number of variables. The research used is correlation analysis with a cross sectional approach, meaning that the measurement of variables is only done once at a time. The population in this study were all children under five who were categorized as stunting in the UPT Puskesmas Ulaweng Kec. Ulaweng. So that the number of samples is determined as many as 15 people. Results: The results showed that there was a relationship between parental knowledge of the provision of supplementary food (PMT) to stunting toddlers at UPT Puskesmas Ulaweng, with the results of the chi square test statistical test obtained p-value = 0.018 P < 0.05, there was a relationship between giving Supplementary food (PMT) given to stunting toddlers at UPT Puskesmas Ulaweng, with the results of the chi square test statistic, p-value = 0.038 P <0.05. Conclusion: There is a relationship between parental knowledge and supplementary feeding (PMT) in stunting toddlers.